(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Education is vital component of human capital formation. Its development put forward the socio economic developments of the country also enhance the political awareness among the society. Therefore, quality education is very much necessary for the development of the entire country. This paper examines the students’ quality in primary education in Paschim Medinipur district of West Bengal. The study is based on primary survey on 305 students from 7 schools scattered over different regions in the district. The study tries to identify the influencing factors of students’ academic performance. The results find moderate performance of students in reading ability and simple numeracy. Parental occupation and mother’s education are found significant influencing determinants of students’ academic performance.